Literacy And Sanctions Predict Land Tax Compliance Without Digitalization Moderation Support: Literasi Dan Sanksi Memprediksi Kepatuhan Pajak Bumi Tanpa Dukungan Moderasi Digitalisasi - Kusmayasari, Dewi; Hadi, Abdul; Hanjaya, Yahya Kurnia; Rosyida, Isnaini Anniswati (Academia Open, 2026)
General Background Taxation serves as a fundamental instrument for financing state development and ensuring economic stability. Specific Background In Bojonegoro Regency, adherence to rural and urban Land and Building Tax payments remains notably low, reaching only 60 percent in 2022 amid various administrative constraints. Knowledge Gap While recent literature emphasizes technological transformation in revenue administration, it remains uncertain whether digital systems successfully govern the relationship between fundamental taxpayer knowledge, penalties, and payment adherence in rural settings. Aims This study investigates the direct role of fiscal knowledge and administrative penalties on property revenue adherence, while explicitly examining technological platform integration as a moderating variable. Results Based on Partial Least Squares Structural Equation Modeling of 87 respondents, both fundamental knowledge and strict penalties positively and significantly predict payment adherence, mutually explaining 66.6 percent of the behavioral variance. Conversely, technological platforms failed to significantly govern the relationship between either regulatory knowledge or penalties and actual payment fulfillment. Novelty This research demonstrates that in specific rural demographics, foundational fiscal comprehension and consistent penalty enforcement dictate behavioral adherence independently of technological adoption. Implications Regional governments must prioritize direct education and firm law enforcement to secure regional revenue, alongside parallel efforts to provide technological infrastructure assistance for rural citizens. Highlights Fundamental fiscal knowledge positively shapes property payment behavior in rural regions. Strict administrative penalties successfully enforce obligation fulfillment among registered citizens. Technological platforms fail to strengthen the connection between regulatory understanding and revenue collection. Keywords Tax Literacy; Tax Sanctions; Taxpayer Compliance; Land And Building Tax; Tax Digitalization